Application of tannin-based coagulant for high-range turbidity surface water clarification. (18th October 2022) - de Oliveira, Camila; Trevisan, Viviane; Skoronski, Everton
Abstract: This study aimed to evaluate the performance of a tannin-based coagulant in clarifying drinking water from a high-range turbidity river and characterizing the sludge. Tanfloc MTH product was selected for this investigation. The study site was surface water located in southern Brazil (Caveiras River, Brazil). Samples were collected just before the Parshall flume in the municipal water treatment plant in Lages (Brazil) for nine months, at least once a week. Jar testing evaluated turbidity removal, alkalinity consumption, optimal coagulant dosage, and settling velocity. After flocculation and settling, the sludge generated from the jar test was submitted to metal and thermogravimetric analyses. The use of tannin reduced the average water turbidity from 26.1 ± 56.1 to 0.94 ± 0.26 NTU, apparent color from 145 ± 190 to 3 ± 3 Pt-Co, and there was no variation in the pH. Additionally, the settling velocity of the flocs reached a maximum turbidity removal at 3.5 cm·min −1 . Furthermore, the metal concentrations in the sludge showed a majority of aluminum and iron, and thermogravimetric analysis revealed 64% weight loss. In conclusion, Tanfloc presented the potential to be used in surface water clarification from the Caveiras river, and the extensive turbidity range observed during this study did not affect the operational stability. HIGHLIGHTS: Tannin-based coagulant was applied to clarify a high-range turbidity superficial freshwater. Treated water showed a lower coefficient of variation for turbidity than raw water. Flocs have a settling velocity comparable to the design criteria value for settling tanks. Potential land application of sludge in terms of metal concentration. Thermogravimetric analysis revealed a weight loss of 64% up to 800 °C. Graphical Abstract